Assessing Student-Designed Teaching Materials in a Learning Material Development Course - Wahyuni, Sri; Nugrahani, Dyah; Pusari, Ratna Wahyu; Fatimah, Siti (Universitas Muria Kudus, 2025)
English Education Study Program students of UPGRIS are required to attend the Learning Material Development (LMD) course. In this class, students are learning about preparing material dan teaching media for English classes. The final product of the course is handouts as the teaching materials, designed according to the guidelines provided by the lecturer. However, the teaching materials resulting from the design need to be assessed to determine their suitability or acceptability as teaching materials that can be used by stakeholders. The purpose of this study is to describe the results of the assessment of teaching materials in the Learning Material Development course of the English Education Study Program, Universitas PGRI Semarang. The assessment of teaching materials is carried out through several stages, namely 1) evaluation of material presentation, 2) linguistic evaluation, 3) evaluation of teaching material content, and graphic evaluation. Furthermore, the evaluation data is described qualitatively. Based on the research, it can be concluded that: 1) the teaching materials are declared feasible for publication, and it is declared that the two material experts, 2) the teaching materials are concluded to have the materials presentation feasibility, and also feasibility for language, content, and graphics.